Cytoskeletal remodeling dynamics - Mierke, Claudia (Physics of Cancer, 2018)
The identification of how cells in 3D microenvironments or natural tissues sense and respond to biophysical stimuli is a longstanding challenge in the physics of cancer and tissue engineering. Cytoskeletal remodeling dynamics are involved in many cellular processes, such as cell motility, transendothelial migration and cell-matrix or cell-cell adhesion receptor recycling. In particular, the connection between the cell's cytoskeleton and the surrounding microenvironment is crucial for the proper function of the cells, including the mechanical properties regulating cellular motility. In this chapter, a strategy is provided to analyze morphological and mechanical responses of contractile cells, such as fibroblasts or cancer cells, in a 3D microenvironment. The cells are able to react to mechanical stimulation such as cell stretch through specific, cell-wide mechanisms such as a staged retraction, cell stiffening and reinforcement. Cellular retraction responses upon mechanical cell stretch occurred for all orientations of stress fibers and cellular protrusions relatively independent of the stretch direction, whereas the reinforcement responses, including the extension of cellular processes and enhanced stress fiber formation, occurred predominantly in the direction of the stretch in order to withstand deformation or stretching. An unreported role of F-actin clumps has been seen, in which clumps act as possible F-actin reservoirs for retraction and reinforcement responses during stretch. These responses upon stretch seem to be related to a model of cellular sensitivity to local physical cues. Moreover, these observations suggest mechanisms for the global actin cytoskeletal remodeling in nonmuscle cells and hence provide insights into cellular responses acting in pathologies such as fibrosis, hypertension or cancer including metastasis.
CRIS-Team WoS Importer:2019-08-27